Rehabilitación ecológica, reserva Thomas Van Der Hammen (2017)
This approach seeks to submit an alternative of occupation within the Thomas van der Hammen reserve, and for this purpose, comes from the consideration the current situation of the reserve, not only of their modes of occupation but the types of possible connectivities between the diverse ecosystems raised there. The article presents some of the stages in the process of research were reached, as well as the impacts of one of the current uses, the breeding grounds; the effect that this use has on present wetlands in the reserve is revised, seeking that the proposal proposes a restructuring process of the forms of occupation to reduce the impact on the ground.